REHYDRATE - an international HELPING working group to REtrieve historical HYDRologic dATa and Estimates - Bertola, M.; Mazzoglio, P.; Gelebo, A. H.; Shobha, A. R.; Jampani, Mahesh; Singh, S.; Prieto, C.; Panda, S.; Zaifoglu, H.; Bhowmik, A.; Guesri, M.; Dietrich, S.; et al. (2024)
Historical hydrological observations are often stored in printed documents and volumes of archives worldwide. This makes them practically inaccessible and unusable for modern hydrological studies as well as puts them at risk of permanent loss due to the deterioration of their medium. In addition to the intrinsic value of rescuing past observations, having access to historical data is essential for understanding better the complexity and changes in the hydrological cycle and its extremes.